The Impact of Career Systems, Motivation, and Work Discipline on The Performance of Foundation Lecturers at Private Higher Education in Bali Province through Job-Insecurity - I Nengah Sudja (EduLine: Journal of Education and Learning Innovation, 2023)
This study attempts to explain the influence of the career system, motivation, and discipline on the performance of foundation lecturers at private tertiary institutions in the Province of Bali through job-insecurity. The objects of observation were four large private tertiary institutions in Denpasar, namely: Warmadewa University, National Education University, Mahasaraswati University, Ngurah Rai University, and Mahendradatta University. From the five universities, 40 foundation lecturers were selected, so the number of respondents = 200 foundation lecturers. The analytical method used is the structural equation model (SEM), with exogenous variables: career system, motivation and work discipline; endogenous variables: lecturer performance; and the intervening variable: job-insecurity. Research findings and results show that: (1) a good career system has a significant positive effect on the performance of PTS foundation lecturers; (2) motivation to become lecturers with higher quality has a significant positive effect on the performance of PTS foundation lecturers; (3) work discipline has no significant effect on the performance of PTS foundation lecturers; (4) the career system has a significant negative effect on job-insecurity; (5) motivation has a significant negative effect on job-insecurity; (6) work discipline has no significant effect on job-insecurity; and (7) job-insecurity has a significant negative effect on the performance of PTS foundation lecturers in Bali Province. (3) work discipline has no significant effect on the performance of PTS foundation lecturers; (4) the career system has a significant negative effect on job-insecurity; (5) motivation has a significant negative effect on job-insecurity; (6) work discipline has no significant effect on job-insecurity; and (7) job-insecurity has a significant negative effect on the performance of PTS foundation lecturers in Bali Province. (3) work discipline has no significant effect on the performance of PTS foundation lecturers; (4) the career system has a significant negative effect on job-insecurity; (5) motivation has a significant negative effect on job-insecurity; (6) work discipline has no significant effect on job-insecurity; and (7) job-insecurity has a significant negative effect on the performance of PTS foundation lecturers in Bali Province.